Profitability and production of VS-535 corn in response to chemical and biological fertilization - Aguilar Carpio, Cid; Arriaga Rubio, Luz María; Cervantes Adame, Yessica Flor; Arenas Julio, Yasmani Rafael; Escalante Estrada, José Alberto Salvador (Acta Universitaria, 2022)
Corn is the most important crop for Mexican farmers; however, low yields and high costs generate low profitability in the crop, so biological products could improve production in the crop. Aiming to determine the effect of chemical and biological fertilization on the profitability, growth, and yield of VS-535 corn, this study was carried out under irrigation conditions in the ejido of Cacahuatlan, municipality of Tlayacapan, Morelos, Mexico. A random complete block design and four repetitions were used. Five Rhizophagus irregularis application treatments were evaluated in association with chemical fertilization. The variables under study were subjected to an analysis of variance, comparison of Tukey means, regression analysis, and profitability. The results show that the 100% chemical fertilizer in association with Rhizophagus irregularis promoted the best height, leaf area, dry weight, and profitability. The highest grain yield and weight was achieved with 100% + Rhizophagus irregularis fertilization, as well as with 100% chemical fertilization.